2016
DOI: 10.1177/0883073816635747
|View full text |Cite
|
Sign up to set email alerts
|

Moyamoya Syndrome in South African Children With HIV-1 Infection

Abstract: A national multicenter study identified 17 South African children with vertically acquired HIV-1 infection and HIV-associated vasculopathy. Five of the children (all indigenous African ancestry) had progressive vascular disease, consistent with moyamoya syndrome. Median presentation age 5.8 years (range 2.2-11). The children with moyamoya syndrome presented with abnormal CD4 counts and raised viral loads. Clinical features included motor deficits, neuroregression, and intellectual disability. Neuroimaging supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 16 publications
0
7
1
Order By: Relevance
“…Only 50 out of 104 patients had diagnostic MRA which revealed features of Moyamoya syndrome in 48 (96%) patients., this study seems to include the highest number of Moyamoya patients reported in the African continent in literature. Hammond et al reported only 17 patients of Moyamoya disease with acquired HIV infection in South Africa which is more than two folds lower than our study population [ 13 ]. A systematic review and meta-analysis conducted by Noubiaq et al explained the lack of data as a consequence of the unaffordability of specific diagnostic tools for Moyamoya disease [ 14 ].…”
Section: Discussioncontrasting
confidence: 57%
“…Only 50 out of 104 patients had diagnostic MRA which revealed features of Moyamoya syndrome in 48 (96%) patients., this study seems to include the highest number of Moyamoya patients reported in the African continent in literature. Hammond et al reported only 17 patients of Moyamoya disease with acquired HIV infection in South Africa which is more than two folds lower than our study population [ 13 ]. A systematic review and meta-analysis conducted by Noubiaq et al explained the lack of data as a consequence of the unaffordability of specific diagnostic tools for Moyamoya disease [ 14 ].…”
Section: Discussioncontrasting
confidence: 57%
“…38,39 HIV is known to cause cerebral vasculopathy, 40 angiitis, 41 aneurysmal dilatation 42 (particularly fusiform aneurysms in children 43 ), arterial stenosis complicated by ischemic infarction, 44 and secondary moyamoya syndrome. 45 Although there is significant literature on HIV-associated cerebrovascular disease, its precise mechanism is not known. 24,36,46 Adult studies have found that stroke is not common in HIV without an additional underlying disease state.…”
Section: Discussionmentioning
confidence: 99%
“…On further analysis, we found several other reports of post-infectious moyamoya, including quaternary neurosyphilis in 1989 [ 204 ] and Haemophilus influenaze type C meningitis in Texas in 2003 [ 205 ]. Moreover, one national multicenter study identified five South African children (four girls of indigenous African ancestry) with human immunodeficiency virus-associated vasculopathy and MMS [ 206 ], and a Canadian and US cohort demonstrated an association between moyamoya and tuberculosis in 1997 [ 196 ]. Finally, a patient with acquired immunodeficiency syndrome was reported as presenting concurrently with moyamoya [ 207 ].…”
Section: Reviewmentioning
confidence: 99%